GE_GERICHTE P/8475/2021 vom 13. Februar 2023 - GE Cour de justice (2023)
ESCROQUERIE;CONCOURS D'INFRACTIONS;FIXATION DE LA PEINE;RESTITUTION(EN GÉNÉRAL) | CP.251; CP.146; CP.49; CP.47; CP.52; CPP.267.al3; OCaS-COVID-19.23